Cationic facial amphiphiles: a promising class of transfection agents. - Walker, S (1996)
A promising class of compounds for DNA transfection have been designed by conjugating various polyamines to bile-acid-based amphiphiles. Formulations containing these compounds were tested for their ability to facilitate the uptake of a beta-galactosidase reporter plasmid into COS-7 cells. Dioleoyl phosphatidyl ethanolamine (DOPE) formulations of some of the compounds were several times better than Lipofectin at promoting DNA uptake. The most active compounds contained the most hydrophilic bile acid components. The activity is clearly not related to affinity for DNA: the hydrophobic bile acid conjugates were found to form stable complexes with DNA at lower charge ratios than the hydrophilic conjugates. We suggest that the high activity of the best compounds is related to their facial amphiphilicity, which may confer an ability to destabilize membranes. The success of these unusual cationic transfection agents may inspire the design of even more effective gene delivery agents.